Less locus coeruleus degeneration and its enhanced influence on neural circuit in Parkinson's tremor - Junyan Sun; Lili Chen; Liang Li; Tao Wu; Tao Feng (Neurobiology of Disease)
Objectives: The involvement of the locus coeruleus in Parkinson's tremor remains unclear. We aimed to decode the role of locus coeruleus in Parkinson's tremor. Methods: We used MRI to examine 120 Parkinson's disease, including 48 tremor-dominant (TD) and 72 postural instability/gait disorder (PIGD), as well as 83 healthy controls. Neuromelanin-sensitive MRI accessed the contrast-to-noise ratio of locus coeruleus. Spectral dynamic causal modeling based on resting-state functional MRI accessed the effective connectivity from locus coeruleus to the cerebello-thalamo-cortical circuit. The pivotal nodes of cerebello-thalamo-cortical circuit included ventral intermediate nucleus, motor cortex, and cerebellum. Results: Both TD and PIGD patients exhibited lower bilateral contrast-to-noise ratio of locus coeruleus than healthy controls. But TD patients had higher contrast-to-noise ratio of locus coeruleus than PIGD, accompanied by increased effective connectivity from locus coeruleus to cerebello-thalamo-cortical circuit than healthy controls and PIGD patients on the more-affected side (P < 0.003125, one-way analysis of covariance). The contrast-to-noise ratio of locus coeruleus and effective connectivity (e.g. locus coeruleus→motor cortex) positively correlated with rest tremor in TD patients (R = 0.47, P = 0.002; R = 0.427, P = 0.003, respectively). Conclusions: TD patients exhibited less locus coeruleus degeneration than PIGD patients, alongside increased influence from locus coeruleus to the cerebello-thalamo-cortical circuit than healthy controls and PIGD patients. The structural/functional alterations of locus coeruleus are closely associated with rest tremor, suggesting the potential for tremor treatment targeting the locus coeruleus noradrenergic system.